2008
DOI: 10.1016/j.juro.2008.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular Invasion of Urothelial Cancer in Matched Transurethral Bladder Tumor Resection and Radical Cystectomy Specimens

Abstract: When lymphovascular invasion is identified in a transurethral bladder tumor resection sample, it will be present in the cystectomy sample in 65% of cases and associated with nodal metastasis in 41%. Lymphovascular invasion is a valuable histological tool in the evaluation of transurethral bladder tumor resection samples, particularly cT2 tumors, because there is significant agreement of lymphovascular invasion status at transurethral bladder tumor resection and at subsequent cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 11 publications
3
28
3
1
Order By: Relevance
“…These results are similar to previous studies of pT1 urothelial cancers removed by RC, in which LVI was found in 5-10% of patients, and was an important prognostic factor for recurrence free survival and CSS. 19,22,23 Additional studies are required to ascertain whether LVI can be reliably and accurately detected in biopsies, and used to identify patients who might benefit from early cystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to previous studies of pT1 urothelial cancers removed by RC, in which LVI was found in 5-10% of patients, and was an important prognostic factor for recurrence free survival and CSS. 19,22,23 Additional studies are required to ascertain whether LVI can be reliably and accurately detected in biopsies, and used to identify patients who might benefit from early cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Methods: We identified all cystectomy patients with muscle-invasive urothelial cancer in Ontario, Canada, 1994-2008. Surgical pathology reports were analyzed for pathological variables including lymphovascular invasion.…”
mentioning
confidence: 99%
“…The prognostic value of lymphovascular invasion (LVI) has previously been investigated by others [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Last year, an interesting study was published revealing significant agreement of lvi status at transurethral bladder tumour resection (tur-tm) and at subsequent cystectomy 3 . In our opinion, histologic evaluation of tur-tm and of cystectomy specimens in terms of the appearance of lvi should provide valuable prognostic data during follow-up.…”
mentioning
confidence: 99%
“…When lymphovascular invasion is identified in a transurethral bladder tumour resection sample, it will be present in the cystectomy sample in 65% of cases and associated with nodal metastasis in 41% 3 . It is not surprising that lvi is identified more frequently in cystectomy specimens, because a far greater amount of tumour is available for examination.…”
mentioning
confidence: 99%